Network analysis of screening and regulation of differentially expressed genes in platelets of patients with myocardial infarction based on bioinformatics - Sheng-Yu Cui (Editorial Board of Journal of Hainan Medical University, 2021)
Objective: To construct a core miRNA regulatory network in peripheral blood platelets of patients with acute myocardial infarction,，and to explore the role of peripheral blood platelet‑related miRNAs in the occurrence and development of acute myocardial infarction. Methods: miRNA and mRNA expression profiling chips were used to screen out differentially expressed miRNA and mRNA. FunRich 3.1.3 software was performed to predict the transcription factors and target genes of differentially expressed miRNA, and then the predicted target genes were intersected with the differentially expressed genes screened by the gene chip. Cytoscape software was applied to construct miRNA-mRNA regulatory network, and we performed KEGG and GO analysis of genes in the regulatory network. Results: A total of 27 differentially expressed miRNAs and 2897 differentially expressed mRNAs were screened through gene expression profiling data. A total of 3563 target genes for differentially expressed miRNAs were predicted, and they were intersected with the differentially expressed mRNAs. After a one-to-one correspondence, there were 503 miRNA-mRNA regulatory relationships. KEGG enrichment and GO analysis of the target genes in the regulatory network showed that these target genes are mainly involved in PI3K-AKT signaling pathway, regulation of actin cytoskeleton, MAPK signaling pathway, human papillomavirus infection, and Ras signaling pathway. GO analysis indicated that the main molecular functions of genes from network included protein macromolecule adaptor activity, molecular adaptor activity, DNA binding transcription repressor activity, etc. Conclusion: We analyzed the miRNA-mRNA regulatory network and the different function in the platelets of acute myocardial infarction and noninfarction populations, and further understood the important role of platelets in the process of acute myocardial infarction, and deepened our understanding of the pathological mechanism of acute myocardial infarction.